1997
DOI: 10.1093/humrep/12.6.1176
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of cryopreserved-thawed pre-embryos in a cycle using exogenous steroids without prior gonadotrophin-releasing hormone agonist suppression yields favourable pregnancy results

Abstract: We have analysed the use of a programmed cycle of administration of exogenous steroids without prior suppression with a gonadotrophin-releasing hormone agonist (GnRHa) for the transfer of cryopreserved-thawed pre-embryos. From July 1992 to June 1994, 199 cycles (162 patients) were studied. Pre-embryos had been previously cryopreserved at the pronuclear stage using 1.5 M 1,2-propanediol as a cryoprotectant. Preparation of the endometrium was achieved in a step-up regime with transdermal oestradiol patches (0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 22 publications
2
23
1
1
Order By: Relevance
“…Three retrospective papers have shown equivalent ongoing pregnancy and live birth rates between NC or modified-NC and AC with GnRH-agonist [28,30,52]. Other three papers have shown that GnRH-agonist administration is irrelevant for endometrial preparation in AC [29,53,54], counteracting a randomized controlled trial that evidenced an improved livebirth rate in AC with GnRH-agonist hormone [25,47]. Levron et al [55] showed that natural endometrium preparation yields better outcome compared with AC cycle, as demonstrated by higher implantation and clinical pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Three retrospective papers have shown equivalent ongoing pregnancy and live birth rates between NC or modified-NC and AC with GnRH-agonist [28,30,52]. Other three papers have shown that GnRH-agonist administration is irrelevant for endometrial preparation in AC [29,53,54], counteracting a randomized controlled trial that evidenced an improved livebirth rate in AC with GnRH-agonist hormone [25,47]. Levron et al [55] showed that natural endometrium preparation yields better outcome compared with AC cycle, as demonstrated by higher implantation and clinical pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…According to Simon et al [28], transfer of frozen-thawed embryos in women with artificially prepared cycles with and without prior GnRHa suppression attributes to no difference on implantation rate as well as on endometrial thickness. Besides, Queenan et al [11] reported that the use of a programmed exogenous hormone cycle for cryopreserved embryo transfer without prior suppression with GnRHa yields favorable pregnancy outcome. Our results indicate that the programmed hormone treatment cycles can be efficiently applied by administering sequential estrogen from day 3 on without preceding GnRHa in women with thin endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, thin endometrium is an extremely poor factor that interferes with an ongoing pregnancy. Some reports suggested canceling the embryo transfer and cryopreserving all the embryos in order to avoid embryo wastage if no favorable endometrial thickness is available [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by progesterone (P4) supplementation for 3 to 6 days before ET [3]. Several studies have questioned the need for GnRH analogues for the pituitary suppression of endogenous ovulation [4][5][6]. Indeed, "natural cycle override" regimens have been used in which high doses of exogenous estrogens are administered during the follicular phase of the natural cycle to prevent a premature LH surge followed by progesterone supplementation for luteal phase support when the endometrium is of adequate thickness( [7].…”
Section: Introductionmentioning
confidence: 99%